Overview of Blood Pressure Changes in Hypertensive Patients using Valsartan at One of Hospital in Jember District - Alvia Putri Priyono, Rosyidatul; Mayasari, Shinta; Khrisna Agung C (Jurnal EduHealth, 2025)
Hypertension is a major global health issue contributing to cardiovascular disease, stroke, kidney failure, and premature death. Its prevalence continues to rise both globally and in Indonesia. Effective management often involves pharmacological treatment, with valsartan, an angiotensin II receptor blocker (ARB), widely used due to its efficacy and safety profile. This study aims to describe blood pressure changes in hypertensive patients treated with valsartan at one of hospital at Jember district. A descriptive observational study was conducted using medical records of patients receiving valsartan therapy from January to October 2022. A total of 4,907 patients were recorded, making hypertension one of the top ten most frequent diagnoses in the hospital. Results showed that valsartan effectively reduced both systolic and diastolic blood pressure, with most patients achieving target levels after treatment. These findings suggest that valsartan is effective in managing hypertension and preventing complications when properly administered and adhered to. Continued monitoring and appropriate treatment selection remain essential for optimal patient outcomes.